2018
DOI: 10.1038/s41598-018-32082-1
|View full text |Cite
|
Sign up to set email alerts
|

A new method to improve the prediction of the celestial pole offsets

Abstract: Knowledge of the Earth’s changing rotation is fundamental to positioning objects in space and on the planet. Nowadays, the Earth’s orientation in space is expressed by five Earth Orientation Parameters (EOP). Many applications in astronomy, geosciences, and space missions require accurate EOP predictions. Operational predictions are released daily by the Rapid Service/Prediction Centre of the International Earth Rotation and Reference Systems Service (IERS). The prediction procedures and performances differ fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Therefore, the increase in RMS for JPL predictions is less steady. However, when going from ultra-short to short-term and mid-term predictions, the increase in JPL prediction errors is less rapid than for the case of Belda et al (2018) predictions. The average RMS reduction compared to the IERS Rapid Service forecasts is lower than for the CPO predictions developed by Belda et al (2018) (19% and 22% for dX and dY, respectively).…”
Section: Resultsmentioning
confidence: 88%
See 4 more Smart Citations
“…Therefore, the increase in RMS for JPL predictions is less steady. However, when going from ultra-short to short-term and mid-term predictions, the increase in JPL prediction errors is less rapid than for the case of Belda et al (2018) predictions. The average RMS reduction compared to the IERS Rapid Service forecasts is lower than for the CPO predictions developed by Belda et al (2018) (19% and 22% for dX and dY, respectively).…”
Section: Resultsmentioning
confidence: 88%
“…The CPO predictions developed by Belda et al (2018) revealed visibly lower RMS prediction errors than official IERS products, reaching about 0.090 mas after 25 days, 0.100 mas after 50 days and about 0.105 mas after 90 days ( Fig. 5 in Belda et al 2018). The average RMS reduction compared to the IERS Rapid Service forecasts was equal to 39.5% for dX and 33.8% for dY.…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations